Practical nursing recommendations for palliative care for people with dementia living in long-term care facilities during the COVID-19 pandemic: A rapid scoping review (2020)
Background: The acute nature of COVID-19 and its effects on society in terms of social distancing and quarantine regulations affect the provision of palliative care for people with dementia who live in long-term care facilities. The current COVID-19 pandemic poses a challenge to nursing staff, who are in a key position to provide high-quality palliative care for people with dementia and their families. Objective: To formulate practice recommendations for nursing staff with regard to providing palliative dementia care in times of COVID-19. Design and method: A rapid scoping review following guidelines from the Joanna Briggs Institute. Eligible papers focused on COVID-19 in combination with palliative care for older people or people with dementia and informed practical nursing recommendations for longterm care facilities. After data extraction, we formulated recommendations covering essential domains in palliative care adapted from the National Consensus Project’s Clinical Practice Guidelines for Quality Palliative Care. Data sources: We searched the bibliographic databases of PubMed, CINAHL and PsycINFO for academic publications. We searched for grey literature using the search engine Google. Moreover, we included relevant letters and editorials, guidelines, web articles and policy papers published by knowledge and professional institutes or associations in dementia and palliative care. Results: In total, 23 documents (7 (special) articles in peer-reviewed journals, 6 guides, 4 letters to editors, 2 web articles (blogs), 2 reports, a correspondence paper and a position paper) were included. The highest number of papers informed recommendations under the domains ‘advance care planning’ and ‘psychological aspects of care’. The lowest number of papers informed the domains ‘ethical care’, ‘care of the dying’, ‘spiritual care’ and ‘bereavement care’. We found no papers that informed the ‘cultural aspects of care’ domain. Conclusion: Literature that focuses specifically on palliative care for people with dementia in long-term care facilities during the COVID-19 pandemic is still largely lacking. Particular challenges that need addressing involve care of the dying and the bereaved, and ethical, cultural and spiritual aspects of care. Moreover, we must acknowledge grief and moral distress among nursing staff. Nursing leadership is needed to safeguard the quality of care and nursing staff should work together within an interprofessional care team to initiate advance care planning conversations in a timely manner, to review and document advance care plans, and to adapt goals of care as they may change due to the COVID-19 situation.